Psychometric and gender invariance analysis of the flourishing scale in the Malaysian context - Chua, Bee Seok; Getrude C. Ah Gang @ Grace; Shazia Iqbal Hashmi; Carmella E. Ading (SAGE Publications, 2022)
The Flourishing Scale is a new scale designed to measure psychological well–being. FS has been translated into more than 10 languages (e.g., Portuguese, Russian, Turki, Spanish, Egyptian, French, Chinses, Japanese, Malay, Urdu, and Persian). The psychometric analysis of the Flourishing Scale has not been explored in the Malaysian context. The aims of the current study were to examine the factor structure, reliability, concurrent validity (correlate with Satisfaction with Life Scale [SWLS] and Life Project Reflexivity Scale [LPRS]) of the Flourishing Scale (FS). The EFA was conducted to explore the factor structure of FS in the Malaysian context. Then, CFA was run to test the model fit of the FS in the Malaysian context. Test of measurement invariance was also conducted to ascertain the generalizability of the factor structure of FS across gender groups. A cross-sectional survey with 663 university students (435 female students and 228 male students) from a public university in Sabah, Malaysia was conducted. The EFA results revealed a single factor solution with a total explained variance of 68.31%. The CFA result also revealed a one-factor structure with all eight items loaded in one factor. The multi-group analysis of this model demonstrated invariance by gender. FS also demonstrated high reliability and good concurrent validity. The FS was positively and significantly correlated with Satisfaction with Life Scale scores, Life Project Reflexivity Scale score and its subscale. The results supported FS appears to be a valid measure of a flourishing state, and its utilities in the Malaysian context is proven, including gender comparisons.